Hepatitis associated with amoxycillin-clavulanic acid combination report of 15 cases. Issue 3 (March 1992) - Larrey, D; Vial, T; Micaleff, A; Babany, G; Morichau-Beauchant, M; Michel, H; Benhamou, J P
Abstract : Fifteen cases of hepatitis related to a combination of amoxycillin and clavulanic acid are reported. Most patients were aged 60 years or more and there were more men than women (sex ratio 4:1). The amoxycillin-clavulanic acid had been given at doses ranging from 0.5 to 6 g/day (mean 2 g/day) for seven to 60 days (mean 18 days). In 11 cases, the first symptoms appeared one to four weeks after stopping treatment. Jaundice was observed in all patients and was frequently associated with pruritus. Serum aminotransferase activities were increased in all patients and were generally two to 10 times the upper limit of normal. Serum alkaline phosphatase activity was considerably increased, from two to seven times the upper limit of normal. Histological examination of the liver, performed in seven patients, showed centri- or panlobular cholestasis in all cases, associated with granulomatous hepatitis in one. The prognosis of amoxycillin-clavulanic acid induced hepatitis seemed to be good. None of the patients exhibited biological or clinical features of hepatic failure and the course of the disease was characterised by the resolution of jaundice within one to eight weeks and a complete recovery within four to 16 weeks. Taking into account the number of treated subjects and reported cases, we estimated the risk of developing hepatitis with this drug combination to be very low, probably below 1/100, 000. Our data suggest that the risk of hepatotoxicity may be increased in elderly men given lengthy treatment. The association of hepatitis and signs of hypersensitivity may suggest an immunoallergic mechanism of hepatotoxicity in some patients.